2019
DOI: 10.3389/fgene.2019.00512
|View full text |Cite
|
Sign up to set email alerts
|

Methylome Dynamics of Bovine Gametes and in vivo Early Embryos

Abstract: DNA methylation undergoes drastic fluctuation during early mammalian embryogenesis. The dynamics of global DNA methylation in bovine embryos, however, have mostly been studied by immunostaining. We adopted the whole genome bisulfite sequencing (WGBS) method to characterize stage-specific genome-wide DNA methylation in bovine sperm, immature oocytes, oocytes matured in vivo and in vitro , as well as in vivo developed single embryos at the 2-, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
59
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 86 publications
6
59
1
Order By: Relevance
“…The demethylation/de novo methylation cycle is expected during normal preimplantation development to remove parental marks, except for imprinted genes and some repetitive elements that remain methylated, and is essential to support the development of a new set of unspecialized pluripotent cells [1,[18][19][20][21]. In this work, we observed that in fast embryos, the demethylation/de novo methylation pattern is more similar to that described in the literature for in vivo and in vitro bovine embryos [22][23][24]. Slow embryos, on the other hand, presented a progressive increase in DNA methylation due to the first cleavages and a decrease in 5hmC throughout development, demonstrating the inability of these embryos to correctly promote DNA demethylation between the two-cell and blastocyst stages.…”
Section: Discussionsupporting
confidence: 71%
“…The demethylation/de novo methylation cycle is expected during normal preimplantation development to remove parental marks, except for imprinted genes and some repetitive elements that remain methylated, and is essential to support the development of a new set of unspecialized pluripotent cells [1,[18][19][20][21]. In this work, we observed that in fast embryos, the demethylation/de novo methylation pattern is more similar to that described in the literature for in vivo and in vitro bovine embryos [22][23][24]. Slow embryos, on the other hand, presented a progressive increase in DNA methylation due to the first cleavages and a decrease in 5hmC throughout development, demonstrating the inability of these embryos to correctly promote DNA demethylation between the two-cell and blastocyst stages.…”
Section: Discussionsupporting
confidence: 71%
“…Nevertheless, average quantification of genomic features exhibited similar differences in Epp oocytes compared with Mpp and CH oocytes, with global methylation levels being lower in Epp samples and differences between features being conserved across all biological conditions. Interestingly, methylation levels in CpG islands were overall lower than in other features, as has been previously observed in bovine oocytes 22 . A similar methylation level in CpG islands and differential clustering within certain conditions have also been described from the whole-genome bisulfite sequencing of pig embryos, although levels of global methylation between oocytes and embryos are not comparable, as the latter undergoes extensive demethylation 23 .…”
Section: Discussionsupporting
confidence: 69%
“…In the present study, the overall organization of genomic feature methylation of Epp oocytes was conserved compared with Mpp and CH oocytes, with slight hypomethylation in both comparisons. Interestingly, we report higher oocyte methylation levels, as well as lower non-CpG methylation levels, than previously described in bovine oocytes 11,22 using both reduced representation bisulfite sequencing (RRBS) and whole genome bisulfite sequencing (WGBS) techniques, which have been reported to generate different average methylation levels 24 . Additionally, both CpG and non-CpG methylation levels in somatic cells (e.g., fibroblasts) have been reported to be lower 25 than oocytes 26 .…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The reprogramming cycle of primordial germ cells is barely described in bovine, however, in mouse, it is known that the genome of primordial germ cells is demethylated and a new profile is established with specific patterns for male or female gametes (Seisenberger et al, 2012;Saadeh and Schulz, 2014). The resulting sperm cells and oocytes have higher levels of DNA methylations than somatic cells and, for bovines, male gametes present even greater number of 5mC than the female ones (Zhang et al, 2016;Duan et al, 2019).…”
Section: Dna Methylation/demethylation In Bovine Embryosmentioning
confidence: 99%